A new genus of Eucharitidae (Hymenoptera: Chalcidoidea), with notes on life history and immature stages - Torréns, Javier; Heraty, John M. (Zootaxa, 2013)
Neolirata new genus (Eucharitidae: Eucharitini) is recognized based on males and females, with new descriptions of eggs, planidia and pupae. Redescriptions are provided for N. alta (Walker) and N. daguerrei (Gemignani) (comb. nov. trans-ferred from Lirata) and a new description of N. furcula sp. nov. is presented. Females of N. alta deposit their eggs on the underside of leaves of Pseudabutilon virgatum (Cav.) Fryxell (Malvaceae) and N. daguerrei on the underside of Urvillea chacoensis Hunz (Sapindaceae). A key to species is included.